Transformation: Dynamic Worldview or Repressive Ideology? - Walsh, Brian J. (Journal of education & Christian belief, 2000)
CHRISTIAN DISCOURSE AROUND education is often preoccupied with issues of ‘transformation’ and ‘worldview’. In a postmodern cultural climate, however, worldviews are seen to invariably legitimate conservative, non-transformational ways of thinking and praxis. Worldview, as a species of totality thinking and metanarrative, is repressive. This article delineates how a dynamically transformational worldview can indeed become a repressive ideology, and then suggests ways in which a worldview can remain dynamically open, engendering a transformational educational practice.